Surface dimensional metrology by optical triangulation - Costa, Manuel F. M. (2016)
Non-destructive dimensional inspection of surfaces is an issue of utmost importance in a large number of situation in R&D and in the industrial world. An increasing number of surfaces and surface types must be microtopographically characterized in non-invasive ways. Optical triangulation in different approaches allow the establishment of metrological systems that by its inherent relative simplicity versatility robustness and reliability can cope with most modern requirements of the non-invasive inspection of objects and surfaces both smooth or rough. In this communication we will present a brief review of the work done at the Microtopography Laboratory of the Physics Department of the University of Minho, Portugal, on the development of methods and systems of optical triangulation based microtopographic inspection of surfaces.